2018
DOI: 10.2217/nnm-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Promising Therapeutic Effect of Gold Nanoparticles Against Dinitrobenzene Sulfonic Acid-Induced Colitis in Rats

Abstract: Our study suggested a new therapy for experimental colitis without noticeable drawbacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…A study by Hussein et al [ 131 ] investigated the treatment potential of intravenously administrated GNPs at various sizes (16–25 nm) and doses (40 and 400 μg/kg) in experimental colitis. These data showed that GNP treatments suppressed the inflammatory response by decreasing the pro-inflammatory cytokine levels, including TNF-α and IL-6, which eventually reduced the colon inflammation and diminished the oxidative stress markers.…”
Section: Application Of Gnps In Other Autoimmune Diseasesmentioning
confidence: 99%
“…A study by Hussein et al [ 131 ] investigated the treatment potential of intravenously administrated GNPs at various sizes (16–25 nm) and doses (40 and 400 μg/kg) in experimental colitis. These data showed that GNP treatments suppressed the inflammatory response by decreasing the pro-inflammatory cytokine levels, including TNF-α and IL-6, which eventually reduced the colon inflammation and diminished the oxidative stress markers.…”
Section: Application Of Gnps In Other Autoimmune Diseasesmentioning
confidence: 99%
“…These results confirmed our investigations that applying GNPs to IA delivery was a potential technique for improving treatment efficacy and compliance in patients with RA [ 26 ], where GNPs appeared to block production of proinflammatory IL-6 cytokines in Jurkat and U937 cells due to a decrease in phosphorylation of extracellular signal-regulated kinases (ERK). In addition, previous results illustrated that coupling with GNPs could add an immunomodulatory function to the conjugated drug by impairing the production of pro-inflammatory cytokines [ 27 ]. Moreover, a previous review had shown an increase in anti-inflammatory cytokine IL-10 secretion from macrophages, in a dose dependent manner of GNPs, in the hepatic injury rat model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this synthesis, citrate ions act as reducing agent and stabilizer (Kong et al 2017 ); furthermore, the negative charge of citrate ions repels AuNPs from each other. The size of gold nanoparticles formed depends on the sodium citrate concentration, salt of gold, temperature, and boiling duration (Hussein and Saleh 2018 ).…”
Section: Methodsmentioning
confidence: 99%